2020
DOI: 10.34172/jcs.2020.030
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Activation Therapy on Reward Seeking Behaviors in Depressed People: An Experimental study

Abstract: Introduction: Behavioral activation therapy (BAT) is designed to help individuals’ approach and access sources of positive reinforcement in their life, which can serve a natural antidepressant function and efforts to help depressed people reengage in their life through focused activation strategies. Methods: In this study, 60 individuals were selected and randomly assigned to intervention and control groups. The intervention group received behavioral activation treatment, including eight treatment sessions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although to our knowledge, no interventions explicitly target BIS sensitivity, certain interventions target and have been observed to alter reinforcement sensitivity (e.g., Cognitive Remediation Therapy targets punishment sensitivity and Transcranial Magnetic Stimulation targets reward sensitivity) [141,142]. Other interventions do not target reinforcement sensitivity but have been shown to reduce BIS sensitivity (e.g., Behavioral Activation Therapy and certain mindfulness types) [143,144]. Pharmacological treatments, e.g., anxiolytic drugs also reduce BIS sensitivity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although to our knowledge, no interventions explicitly target BIS sensitivity, certain interventions target and have been observed to alter reinforcement sensitivity (e.g., Cognitive Remediation Therapy targets punishment sensitivity and Transcranial Magnetic Stimulation targets reward sensitivity) [141,142]. Other interventions do not target reinforcement sensitivity but have been shown to reduce BIS sensitivity (e.g., Behavioral Activation Therapy and certain mindfulness types) [143,144]. Pharmacological treatments, e.g., anxiolytic drugs also reduce BIS sensitivity [36].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Karimpour et al . [ 34 ] reported that BAT significantly reduced depression and rumination in the post-test and two-month follow-up stages. Also, Soleimani et al .…”
Section: Discussionmentioning
confidence: 99%
“…Second, BAS is closely related to reward seeking, and individuals with high-BAS sensitivity have a higher preference for novelty processing and reward dependence ( 94 ). They are highly motivated by both external and internal rewards and are able to devote themselves to an activity in which they feel a sense of pleasure and control ( 95 ). Thus, high-BAS individuals may have a higher desire to explore perceived goals, and uncertain situations may be perceived as novel and rewarding stimuli.…”
Section: Discussionmentioning
confidence: 99%